Heterogeneous Interaction Effects of Digital Technology Innovation and Urban-Rural Income Inequality on City-Level Carbon Emissions - Chen Liang; Zhao Jiancong; Kang Tingting; Li Zeng; Lin Gang (Redai dili)
In this study, we used the optimal parameters-based Geographical Detector Model to investigate how digital technological innovations, urban-rural income inequality, energy efficiency, and their interactions affect urban carbon emissions in China. Data from 279 cities during 2005, 2010, 2015, and 2019 were used. The finding indicate that: (1) Digital technology innovation (q: 0.159~0.290), gross domestic product per capita (q: 0.249~0.296), and urbanization rate (q: 0.120~0.204) were the main factors driving carbon emissions as single-factor effects, with digital technology innovation becoming increasingly significant over time. (2) At the national level, the relationship between digital technology innovation and urban-rural income inequality followed an N-shaped curve, initially intensifying then weakening and intensifying again (q: 0.202~0.303). Regionally, the interaction shifted from nonlinear weakening to bivariable enhancement in the northeast (q: 0.325~0.802), whereas it strengthened continuously in the central (q: 0.278~0.512) and western regions (q: 0.198~0.588). In contrast, the interaction transitioned from bivariable enhancement to nonlinear weakening in the east (q: 0.056~0.301). Notably, in 2015, the q value of this interaction was 0.056, which was only three-tenths of the unidirectional effect of urban-rural income inequality, thereby indicating that the interaction between digital technology innovation and urban-rural income inequality can suppress carbon emissions. This suggests that, in the path towards achieving carbon neutrality, it is crucial to fully leverage the role of digital innovation technology, reduce urban-rural income inequality, and, more importantly, harness their combined effect to lower urban carbon emissions.